Wildfire & insurance - Colorado State Forest Service, author (Colorado State University. Libraries, 2007)
Wildfire is a growing threat in the Rocky Mountain Region. To help protect themselves and their property, homeowners need to be aware of the importance of mitigating wildfire hazards and be aware of the insurance impact of living in high-risk areas.
Keywords: tree thinning; brush thinning; disaster mitigation; Colorado